Evidence for X (3872) →j/ψ π+ π-produced in single-tag two-photon interactions. - Bhardwaj, Vishal; Patra, Sourav (American Physical Society, 2021)
lectron or the positron in the final state, exploring the highly virtual photon region. The search is performed in eþe− → eþe−J=ψπþπ−, using 825 fb−1 of data collected by the Belle detector operated at the KEKB eþe− collider. We observe three Xð3872Þ candidates, where the expected background is 0.11 0.10 events, with a significance of 3.2σ. We obtain an estimated value for Γ˜ γγB(Xð3872Þ → J=ψπþπ−) assuming the Q2 dependence predicted by a cc¯ meson model, where −Q2 is the invariant mass squared of the virtual photon. No Xð3915Þ → J=ψπþπ− candidates are found
Only IISER Mohali authors are available in the record.
Keywords: Particle Production